Formulasi Sediaan Pewarna Pipi Dari Ekstrak Daun Jawer Kotok (Plectranthus scutellarioides (L.) R.Br) Dalam Bentuk Compact Powder - Susanti, Laila; Widodo, Subur; Nurjanah, Siti; Sivitha, Sivitha (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2023)
Blush on was cosmetic used to color the cheeks so that it can improve fresh impression in makeup. Plectranthus scutellarioides (L.) R.Br has anthocyanin content could be used as a natural dye. This research aims to make a rouge from Plectranthus scutellarioides (L.) R.Br extract in the form of compact powder. To get Plectranthus scutellarioides (L.) R.Br extraction we had to macerate 3 kilogram Plectranthus scutellarioides (L.) R.Br into 96% etanol liquid then the maserate is evaporated with rotary evaporator to obtained thick extract. Further more rouge were formulated with kaolin, talc, zinc stearate, oleum rosae, isopropyl myristate, lanolin, and nipagin. Plectranthus scutellarioides (L.) R.Br extract with variations in concentration 6% (F1), 8% (F2) and 10% (F3). After that could be evaluated (color dispersion test, crack test, polishing test, irritation test, hedonic test, and stability test. The results from Plectranthus scutellarioides (L.) R.Br extract result color light brown for F1, red brown for F2 and dark red for F3. Based on the test result all formulation had a homogeny color, not cracked in the crack test qualify for the irritation test. Dosage formulations with concentration 10% many liked. While on the method low temperature stability all preparations no changed organoleptic (color, smell and shape) but in the test high temperature stability of all formulations the preparation has a slight discoloration at thefourth week. The color looks faded not like the beginning. It is because the content of anthocyanin contained in Plectranthus scutellarioides (L.) R.Br extract decreases. Plectranthus scutellarioides (L.) R.Br extract cannot be formulated as a rouge because does not give color in the polish test, powder is rough so the color cannot stick to the skin. Keywords : Plectranthus scutellarioides (L.) R.Br, Coleus atropurpureus (L.) Benth, rounge, formulation